Diaphanous bodies - Colangelo, Jeremy (University of Michigan Press, 2021)
Intro – Contents – Acknowledgments – Abbreviations – Introduction: Tempestuously Able-Bodied – 1. Clear Indistinct Ideas: Narrative, Sensation, and the Diaphanous Body in Joyce's Ulysses – 2. Indolesco Ergo Sum: Language, Compulsion, and Beckett's Existential Pains – 3. Abling Self and Other: Self-Sufficiency and Gender in George Egerton – 4. Unhoused Capacities: Elizabeth Bowen's Colonial Agency – Conclusion: COVID-19 and the Plagues of Absence – Bibliography – Index.
Description based on publisher supplied metadata and other sources
Keywords: Irish literature-20th century-History and criticism; English literature-Irish authors-20th century-History and criticism; People with disabilities in literature; Ability; English literature; Irish literature; Human body in literature; Electronic books; English literature - Irish authors; Criticism; interpretation; etc